The pattern-recognition receptor CORE of Solanaceae detects bacterial cold-shock protein - Wang, Lei; Albert, Markus; Einig, Elias; Fuerst, Ursula; Krust, Damaris; Felix, Georg (Nature Plants, 2016)
Plants and animals recognize microbial invaders by detecting microbe-associated molecular patterns (MAMPs) by cell surface receptors. Many plant species of the Solanaceae family detect the highly conserved nucleic acid binding motif RNP-1 of bacterial cold-shock proteins (CSPs), represented by the peptide csp22, as a MAMP. Here, we exploited the natural variation in csp22 perception observed between cultivated tomato (Solanum lycopersicum) and Solanum pennellii to map and identify the leucine-rich repeat (LRR) receptor kinase CORE (cold shock protein receptor) of tomato as the specific, high-affinity receptor site for csp22. Corroborating its function as a genuine receptor, heterologous expression of CORE in Arabidopsis thaliana conferred full sensitivity to csp22 and, importantly, it also rendered these plants more resistant to infection by the bacterial pathogen Pseudomonas syringae pv. tomato DC3000. Our study also confirms the biotechnological potential of enhancing plant immunity by interspecies transfer of highly effective pattern-recognition receptors such as CORE to different plant families.
CRIS-Team Scopus Importer:2020-03-09